fromage: A library for the study of molecular crystal excited states at the aggregate scale - Rivera, Miguel; Dommett, Michael; Sidat, Amir; Rahim, Warda; Crespo‐Otero, Rachel (Journal of computational chemistry, 2020)
The study of photoexcitations in molecular aggregates faces the twofold problem of the increased computational cost associated with excited states and the complexity of the interactions among the constituent monomers. A mechanistic investigation of these processes requires the analysis of the intermolecular interactions, the effect of the environment, and 3D arrangements or crystal packing on the excited states. A considerable number of techniques have been tailored to navigate these obstacles; however, they are usually restricted to in‐house codes and thus require a disproportionate effort to adopt by researchers approaching the field. Herein, we present the FRamewOrk for Molecular AGgregate Excitations (fromage), which implements a collection of such techniques in a Python library complemented with ready‐to‐use scripts. The program structure is presented and the principal features available to the user are described: geometrical analysis, exciton characterization, and a variety of ONIOM schemes. Each is illustrated by examples of diverse organic molecules in condensed phase settings. The program is available at https://github.com/Crespo-Otero-group/fromage. Accurately modeling the photoexcitations of molecular aggregates involves complementing excited state methodologies with auxiliary calculations. Due to the diversity of chemical and structural space in multimolecular complexes, these calculations require a high degree of adaptability which calls for the use of modular programming tools hitherto unavailable for the investigation of photochemical properties of molecular aggregates. The FRamewOrk for Molecular AGgregate Excitations (fromage), described herein, compiles geometry manipulation tools, exciton state characterization, and QM:QM′ models for geometry optimization.